Detection of human IgG on Poly(pyrrole-3-carboxylic acid) thin film by electrochemical-Surface plasmon resonance spectroscopy - Rapiphun Janmanee (2018)
An electrochemically controlled surface plasmon resonance (SPR) immunosensor for the detection of human immunoglobulin G (IgG) has been developed using poly(pyrrole-3-carboxylic acid) (PP3C) film. In this work, a pyrrole-3-carboxylic acid monomer was used for electropolymerization of a PP3C film on a gold-coated high-refractive-index glass slide. In situ electrochemical (EC)-SPR spectroscopy was performed to study the kinetic property and electroactivity property of the PP3C film. Moreover, ultraviolet-visible (UV-vis) spectroscopy was performed to characterize the PP3C film. Finally, the immunosensor-based PP3C film was constructed. The carboxylic acid surface of the PP3C film was activated for the immobilization of anti-human IgG. The immunosensor electrode was used for probing the binding reaction of anti-human IgG/human IgG with several concentrations of human IgG at different constant applied potentials. The probe immobilization and immunosensing process were in situ monitored by EC-SPR technique. The sensitivity of the sensor was improved by controlling the morphology of the PP3C film by applying the potential. © 2011 The Japan Society of Applied Physics.